Optimizing pomegranate harvest via maturity detection and mechanized settings to improve quality and reduce losses - Anwar, Naglaa S.; Morad, M. M.; Ali, M. M.; El-Latif, Omar. Abd; El-Maghawry, Hend. A. M. (Edelweiss Applied Science and Technology, 2025)
Pomegranate, Punica granatum L., undergoes significant physiological and structural changes during maturation, reflected in its color, total soluble solids, and stem strength. Identifying the optimal maturity stage is essential to maintain fruit quality and minimize postharvest losses. This study evaluated key maturity indices under varying neck moisture levels and developed a low-cost harvesting machine based on those indices. Laboratory tests were performed at 22%, 26%, 36%, and 46% neck moisture to measure shear force, color parameters including L*, a*, b*, chroma, and hue angle, and total soluble solids. The optimal maturity stage was found at 26% moisture, where color development and soluble solids were highest. Field experiments assessed the machine’s performance at four disc speeds ranging from 1100 to 1320 rpm and tilt angles of 0°, 12°, 21°, and 32°. The best results were achieved at 1250 rpm and a 21° tilt, yielding 2520 fruits per hour, 1.71% fruit damage, 0.020 kWh/Mg specific energy, and a harvesting cost of 6.86 US/Mg criterion cost. The developed harvester provides a simple and efficient solution for selective pomegranate harvesting, particularly for small to mid-sized farms.